Hydrothermal plumes in the Gulf of Aden, as characterized by light transmission, Mn, Fe, CH4 and δ13C–CH4 anomalies. (November 2015) - Gamo, Toshitaka; Okamura, Kei; Hatanaka, Hiroshi; Hasumoto, Hiroshi; Komatsu, Daisuke; Chinen, Masakazu; Mori, Mutsumi; Tanaka, Junya; Hirota, Akinari; Tsunogai, Urumu; Tamaki, Kensaku
Abstract: We conducted water column surveys to search for hydrothermal plumes over the spreading axes in the Gulf of Aden between 45°35′E and 52°42′E. We measured light transmission and chemical tracers Mn, Fe, CH4 and δ 13 C of CH4 in seawater taken using a CTD-Carrousel multi-sampling system at 12 locations including a control station in the Arabian Sea. We recognized three types of hydrothermal plumes at depths of 650 to 900 m (shallow plumes), 1000 to 1200 m (intermediate plumes), and >1500 m (deep plumes). The shallow plumes were apparently originated from newly discovered twin seamounts (12°03–06′N and 45°35–41′E) at the westernmost survey area, where two-dimensional distributions of light transmission and Mn were mapped by tow-yo observations of the CTD-sampling system with an in situ auto-analyzer GAMOS. The maximum concentrations of Mn, Fe, and CH4 of 46 nM, 251 nM, and 15 nM, respectively, were observed for collected seawater within the shallow plumes. The intermediate plumes were characterized by anomalies of light transmission, Mn, Fe, and δ 13 C of CH4, but by little CH4 anomalies, suggesting that CH4 had been consumed down to the background level during the aging of the plumes. Anomalies of δ 3 He already reported by the World Ocean Circulation Experiment (WOCE) program exhibited a hydrothermal plume-like peak at 2000 m depth in the Gulf of Aden, which seems to coincide with the deep plumes observed in this study. The endmember δ 13 C–CH4 values for the shallow and the deep plumes were estimated to be in a range between −10‰ and −15‰, demonstrating that the sources of CH4 are not biogenic but magmatic as similarly observed at sediment-starved mid-oceanic ridges.